Characterization of Particulate Matter Collected at Mysore City Roadways in Association with Urban Traffic Condition - , Azis Kemal Fauzie; , G. V. Venkataramana (Archives of Current Research International, 2017)
Aim: To identify the source of particulate matter (PM) emissions in Mysore urban city roadways by characterizing PM of different aerodynamic diameters (PM2.5 and PM10) using various advanced techniques and finding their correlation with site traffic condition. Place and Duration of Study: The study was conducted in urban area of Mysore city, Karnataka, India, from 2014 to 2017. Methodology: Emissions of PM2.5 and PM10 were estimated using mathematical model incorporating number of vehicles and their emission factors. The elemental composition, image interpretation, and size distribution of particles were analyzed comprehensively using energy dispersive X-ray (EDX) spectroscopy, scanning electron microscopy (SEM), and dynamic light scattering (DLS) methods, respectively. Results: PM concentrations were found 2-4 times higher in commercial areas compared to industrial and residential areas, and are considerably correlated (p<0.05) with vehicle traffic and atmospheric temperature. Emissions of PM2.5 and PM10 estimated numerically from road traffic data are significantly correlated (p<0.005 and p<0.0005, respectively) with PM concentrations measured experimentally. DLS and SEM image interpretation showed that about 90% of near-roadway particles were in the size of fine particles (PM2.5) and 74% of them have circularity values above 0.75. EDX analysis found that roadside PM are carbon-rich particles containing 56% black carbon and trace amount of soil-derived particles, sea salts and metal-containing particles. Conclusion: Experimental particle characterization by advanced laboratory analyses and numerical estimation of PM emission using model from road traffic survey both confirmed that fossil-fueled vehicles are the main source of PM emissions in urban area.